Google Cloud Platform for developers : build highly scalable cloud solutions with the power of Google Cloud Platform - Hunter, Ted; Porter, Steven (Packt Publishing, 2018)
The Google Cloud Platform provides auto-scaling compute power and distributed in-memory cache, task queues and data stores to write, build, and deploy Cloud-hosted applications. This book will help you to learn how to integrate the various services to build optimal solutions for your unique business needs using Google Cloud Platform.